The Search for God in the Medieval Novel Laur - Paula-Andreea Onofrei (Anastasis: Research in Medieval Culture and Art)
By offering the consumers of literature a “non-historical novel”, as the writer himself mentioned on the title page, Evgheni Vodolazkin delicately manages to take his reader to a world which is outside the laws of time, although the action is placed in the Middle Ages. As we have mentioned in the review of the book, it is captivating, charming, mesmerizingly beautiful – these would be the essence of this creation. In a nutshell, we consider that Vodolazkin’s words about his own novel invite to meditation, offering a complex perspective: “There are things about which one may speak more esily in the context of old Russia. About God, for example. In my humble opinion, the connections with Him were more direct a long time ago. Furthermore, they simply existed. Now, the nature of these connections represents the preoccupation of very few people, and this leaves us in anxiety. Have we found out, from the Middle Ages onwards, a completely new thing that has allowed us to relax?“